Hybrid Reduced Graphene Oxide/Manganese Diselenide Cubes: A New Electrode Material for Supercapacitors. Issue 11 (5th July 2017) - Balamuralitharan, B.; Karthick, S. N.; Balasingam, Suresh Kannan; Hemalatha, K. V.; Selvam, Samayanan; Raj, J. Anandha; Prabakar, Kandasamy; Jun, Yongseok; Kim, Hee‐Je
Abstract: The integration of 2 D graphene nanosheets and layered transition‐metal dichalcogenides has been recognized as one of the most extensive strategies for the synthesis of promising electrode materials for energy‐storage devices. In this study, cubic manganese diselenide (MnSe2 ) and hybrid reduced graphene oxide/MnSe2 (G‐MnSe2 ) materials were synthesized by a facile hydrothermal method. Metallic selenium impurities are considered to be a major unwanted byproduct in this method. An effective means to remove such bulk chalcogenides is a key challenge. For the synthesis of the G‐MnSe2 hybrid material, we used a strategy in which the graphene oxide was mixed with manganese and selenium precursors. Surprisingly, the final G‐MnSe2 product contained a negligible amount of selenium impurity. The MnSe2 and G‐MnSe2 hybrid materials were characterized in detail. For the first time, the electrochemical energy‐storage behavior of MnSe2 ‐based materials was assessed for supercapacitor applications. The specific capacitance of the MnSe2 electrode was approximately 57.8 mF cm −2, whereas the hybrid G‐MnSe2 electrode showed a much higher specific capacitance of 93.3 mF cm −2 at a scan rate of 1 mV s −1 . A symmetric cell made from the G‐MnSe2 hybrid material showed excellent long‐term stability for 4500 cycles and approximately 106 % retention of its initial capacitance, which is impressive compared with the cycle life of the MnSe2 ‐based symmetric cell (80 % capacitance retention at the 4500th cycle). Abstract : Supercapacitor cubes : Microcubic MnSe2 and hybrid reduced graphene oxide/MnSe2 (G‐MnSe2 ) electrode materials are synthesized by a hydrothermal method. The as‐synthesized materials have good electrochemical charge‐storage properties and long‐term cycle lives.